Constitutive expression of Brassica juncea annexin, AnnBj2 confers salt tolerance and glucose and ABA insensitivity in mustard transgenic plants. (December 2017) - Ahmed, Israr; Yadav, Deepanker; Shukla, Pawan; Vineeth, T.V.; Sharma, P.C.; Kirti, P.B.
Highlights: Overexpression of AnnBj2 resulting in salt stress tolerance is the first report of functional characterization of any annexin in mustard. Constitutive expression of AnnBj2 resulted in ABA and glucose insensitivity in mustard transgenic plants. Constitutively expressed AnnBj2 modulated the expression of genes involved in ABA metabolism at seed germination stage in mustard plants. Mustard transgenic plants exhibited significant downregulation of ABI4 and ABI5 with enhanced expression of CYP707A2. Abstract: Annexins belong to a plasma membrane binding (in a calcium dependent manner), multi-gene family of proteins, which play ameliorating roles in biotic and abiotic stresses. The expression of annexin AnnBj2 of Indian mustard is tissue specific with higher expression in roots and under treatments with sodium chloride and abscisic acid (ABA) at seedling stage. The effect of constitutive expression of AnnBj2 in mustard was analyzed in detail. AnnBj2 OE (over expression) plants exhibited insensitivity to ABA, glucose and sodium chloride. The insensitivity/tolerance of the transgenic plants was associated with enhanced total chlorophylls, relative water content, proline, calcium and potassium with reduced thiobarbituric acid reactive substances and sodium ion accumulation. The altered ABA insensitivity of AnnBj2 OE lines is linked to downregulation of ABI4 and ABI5 transcription factors and upregulation of ABA catabolic gene CYP707A2 . Furthermore, we found that overexpression of AnnBj2 upregulated the expression of ABA-dependent RAB18 and ABA-independent DREB2B stress marker genes suggesting that the tolerance phenotype exhibited by AnnBj2 OE lines is probably controlled by both ABA-dependent and −independent mechanisms.